WHY RESEARCH ON NONCOMMUNICABLE DISEASES IN INDUSTRIALISED POPULATIONS IS NOT ADEQUATE FOR DEVELOPING PUBLIC HEALTH POLICIES IN MODERNISING COUNTRIES - Jonathan Wells (Revista Brasileira de Atividade Física e Saúde)
EDITORIAL